Beneficial effects of abciximab in patients with primary percutaneous intervention for acute ST segment elevation myocardial infarction in clinical practice. Issue 10 (10th April 2006) - Heer, T; Zeymer, U; Juenger, C; Gitt, A K; Wienbergen, H; Zahn, R; Gottwik, M; Senges, J
Abstract : Objectives: To assess the safety and effectiveness of abciximab in patients with ST elevation myocardial infarction (STEMI) treated with primary percutaneous coronary intervention (PCI) in clinical practice. Methods: Data were analysed of 2184 consecutive patients treated with primary PCI for acute STEMI and either concomitant abciximab or no glycoprotein IIb/IIIa inhibitor (control group), who were prospectively enrolled in the Acute Coronary Syndromes (ACOS) registry between July 2000 and November 2002. Results: Patients who were treated with abciximab were younger than the control group, and fewer of them had a history of stroke/transient ischaemic attack and systemic hypertension, but more of them had three-vessel coronary artery disease and cardiogenic shock. Cumulated mid-term survival for patients treated with abciximab was significantly higher than in the control group (91% v 79%, log rank p < 0.05, median observational time 375 days, range 12–34 months). The Cox proportional hazards model of mid-term mortality after admission with adjustment for baseline characteristics showed that mortality was significantly lower in the abciximab group than in the control group (hazard ratio 0.68, 95% confidence interval 0.49 to 0.95). Whereas overall there was no difference in bleeding complications, patients older than 75 years had more major bleeding events with abciximab (12.5% v 3.4%, p = 0.03). Conclusion: In clinical practice adjunctive treatment with abciximab in patients with primary PCI for acute STEMI was associated with a reduction in mid-term mortality. The subgroup of patients older than 75 years who were treated with abciximab had more major bleeding complications.